Analisis Kepuasan Pengguna Terhadap Learning Management System Course Lean Manufacture Menggunakan Metode Importance Performance Analysis - Sania Marcella; Sinta Dewi (International Forum of Researchers and Lecturers, 2024)
User satisfaction can be measured through a variety of methods, including user satisfaction surveys, direct feedback, and analysis of user behavior data. This research aims to analyze user satisfaction withLearning Management System (LMS) Course Lean Manufacturing using methodImportance Performance Analysis (IPA). Through surveys and data analysis of 100 respondents from LMS users, we identified critical attributes that influence user satisfaction. The IPA method is used to assess the level of importance and performance of each attribute, with a focus on determining attributes that have a high level of importance but low performance. The results show that a particular attribute, which we identified as attribute A, has high importance but low performance. Therefore, improvements to attribute A are considered crucial for increasing LMS user satisfactionCourse Lean Manufacturing. The implications of these findings provide guidance for system developers and course organizers to focus on certain aspects to increase the effectiveness and user acceptance of learning platformsLean Manufacturing. This research contributes to further understanding of the factors that influence LMS user satisfaction in learning contextsLean Manufacturing.